Persepsi Masyarakat Prokowinong Terhadap Tradisi Rogomoyo Di Desa Kaliwungu Kabupaten Kudus - Amul Chusni (Jurnal Penelitian dan Pendidikan IPS, 2022)
The Rogomoyo tradition means the custom of replacing the luwur cloth or the tomb of Ms. Rogomoyo in Prokowinong hamlet, Kaliwungu village, Kudus. Untilnow, the Rogomoyo tradition is still maintained and preserved. Every year the people of Prokowinong always hold a tradition as a form of respect for the struggle and services of Mbah Rogomoyo. This study aims to determine the process of implementing the Rogomoyo tradition in Kaliwungu village, Kudus district, describe the values contained in the Rogomoyo tradition in Kaliwungu village, Kudus district, identify and describe community perceptions of the Rogomoyo tradition in Kaliwungu village, Kudus district. This type of research is qualitative research. Data was collected by conducting interviews, literature and observation. From thisstudy, it was found that people's perceptions of the Rogomoyo tradition vary widely, the residents of Prokowinong hamlet, Kaliwungu village, Kudus district also still celebrate the Rogomoyo tradition because itcontains high noble values. The form of implementation pays attention to the traditional system, upholds the values of tolerance, religion and generosity that has been carried out withall communities. the implementation of the Rogomoyo tradition to remember the forerunner to being a forerunner as well as an expert in carpentry so as to be able to produce Kudus traditional houses.